63.7k views
2 votes
2) Use the definition f'(x) = lim

f(x+h)-f(x)
h
to find the derivative.
h-0
f(x) = Vx+ 2

2) Use the definition f'(x) = lim f(x+h)-f(x) h to find the derivative. h-0 f(x) = Vx-example-1
User Yemaw
by
4.6k points

1 Answer

2 votes

lim h→0 f(x + h) − f(x)h= limh→0x+h −4xh= limh→04x−4(x+h)x(x+h)= limh→04hhx(x + h)= limh→04x(x + h)=4x2.

User Mohamed Salah
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.